Harvard Business Review on Advancing Your Career - Harvard Business Review Press (Boston, Massachusetts Harvard Business Review Press, 2011)
If you need the best practices and ideas for achieving career growth and fulfillment-but don't have time to find them-this book is for you. Here are 11 inspiring and useful perspectives, all in one place
Include Index
Keywords: Promotions -- Career development